2011
DOI: 10.1063/1.3610566
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer based system doped with nonlinear optical dye as a medium for amplified spontaneous emission and lasing

Abstract: In this paper, we present results of detailed studies on amplified spontaneous emission (ASE) and lasing achieved in a double-layer system consisted of a biopolymer based matrix loaded with 3-(1,1-dicyanoethenyl1)-1phenyl-4,5dihydro-1H-pyrazole organic nonlinear optical dye and photochromic polymer. The laser action was achieved via distributed feedback configuration with third order of Bragg scattering on surface relief grating generated in photochromic polymer. To excite the luminescence, we have used 6 ns p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 26 publications
1
32
1
Order By: Relevance
“…The periodic corrugation of the thickness (SRG -Surface Relief Grating) of the photochromic bottom layer in a two-layer system where the upper layer is a luminescent one can serve as a Distributed Feedback (DFB) resonator for organic DFB lasers [1][2][3]. The double layer structure used in these devices results in some limitations, like small refractive index contrast on the interface between the polymers, necessity of proper solvent selection for both polymers, and multistep fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…The periodic corrugation of the thickness (SRG -Surface Relief Grating) of the photochromic bottom layer in a two-layer system where the upper layer is a luminescent one can serve as a Distributed Feedback (DFB) resonator for organic DFB lasers [1][2][3]. The double layer structure used in these devices results in some limitations, like small refractive index contrast on the interface between the polymers, necessity of proper solvent selection for both polymers, and multistep fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…Intercalation of dye molecules in DNA strands allowed for dye loading at high concentration and reduced fluorescence quenching, which lowered the threshold for amplified spontaneous emission and lasing [148]. Lasing has been reported in a thin film of DNA doped with Rhodamine 6G dye [149] and in distributed feedback cavities containing DNAs doped with fluorescent dyes [150,151]. DNA was used as a linker of a donor and acceptor fluorescent dyes in an optofluidic laser as a means to control the efficiency of the Förster resonance energy transfer (FRET) between the gain molecules [152].…”
Section: Fluorescent Protein and Organic Dye Lasersmentioning
confidence: 99%
“…Dye doped DNA media have demonstrated amplified spontaneous emission with pulsed laser excitation [11]. Sznitko et al [13] successfully demonstrated amplified spontaneous emission and lasing action in deoxyribonucleic acid blended with cetyltrimethyl-ammonium chloride surfactant and doped with 3-(1,1-dicyanoethenyl1)-1phenyl-4,5dihydro-1H-pyrazole organic dye. Hanczyc et al [14] [15] and in silica films [16] has been investigated recently.…”
Section: Introductionmentioning
confidence: 99%
“…Deoxyribonucleic acid (DNA), a highly nonlinear bioorganic polymer, has been investigated as a photonic material recently with adequate success [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Biomaterials are interesting due to their remarkable properties which are not easily replicated with conventional organic or inorganic materials in the laboratory.…”
Section: Introductionmentioning
confidence: 99%